Correlation of the Patient Reported Outcomes Measurement Information System with Legacy Outcomes Measures in Assessment of Response to Lumbar Transforaminal Epidural Steroid Injections - Shahgholi, L.; Yost, K.J.; Carter, R.E.; Geske, J.R.; Hagen, C.E.; Amrami, K.K.; Diehn, F.E.; Kaufmann, T.J.; Morris, J.M.; Murthy, N.S.; Wald, J.T.; Thielen, K.R.; et al. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: The Patient Reported Outcomes Measurement Information System is a newly developed outcomes measure promulgated by the National Institutes of Health. This study compares changes in pain and physical function–related measures of this system with changes on the Numeric Rating Pain Scale, Roland Morris Disability Index, and the European Quality of Life scale 5D questionnaire in patients undergoing transformational epidural steroid injections for radicular pain. MATERIALS AND METHODS: One hundred ninety-nine patients undergoing transforaminal epidural steroid injections for radicular pain were enrolled in the study. Before the procedure, they rated the intensity of their pain by using the 0–10 Numeric Rating Pain Scale, Roland Morris Disability Index, and European Quality of Life scale 5D questionnaire. Patients completed the Patient Reported Outcomes Measurement Information System Physical Function, Pain Behavior, and Pain Interference short forms before transforaminal epidural steroid injections and at 3 and 6 months. Seventy and 43 subjects replied at 3- and 6-month follow-up. Spearman rank correlations were used to assess the correlation between the instruments. The minimally important differences were calculated for each measurement tool as an indicator of meaningful change. RESULTS: All instruments were responsive in detecting changes at 3- and 6-month follow-up (P < .0001). There was significant correlation between changes in Patient Reported Outcomes Measurement Information System scores and legacy questionnaires from baseline to 3 months (P < .05). There were, however, no significant correlations in changes from 3 to 6 months with any of the instruments. CONCLUSIONS: The studied Patient Reported Outcomes Measurement Information System domains offered responsive and correlative psychometric properties compared with legacy instruments in a population of patients undergoing transforaminal epidural steroid injections for radicular pain. EQ-5DEuropean Quality of Life scale 5D questionnaireNRSNumeric Rating Pain ScalePROMISPatient Reported Outcomes Measurement Information SystemRMDIRoland-Morris Disability IndexTFESItransforaminal epidural steroid injection